Hedges in Biology Research Articles:: What Types and Frequency do Algerian Authors Use ? - Souici , Fairouz; Slougui, Doudja (Journal of Human Sciences, 2022)
This paper aims at examining the use of hedging by Algerian scientists in the research article genre. To this end, a corpus of 31 articles, extracted from 5 Algerian locally published journals in the field of biology was analysed in terms of type, frequency and distribution of hedges across the research article sections. The quantitative analysis indicates that Algerian biologists employ different types of hedges with different proportions. However, main verbs’ category is the most prominent type of hedges in this data. Specifically, non-factive reporting sub-class of verbs is the highest over all other types of hedges. Algerian biologists seem to rely heavily on these verbs as strategical devices to provide support and further evidence to their own findings. Implications of this study can help placing hedging competence as an important rhetorical skill within the context of teaching scientific English.